2011
DOI: 10.1348/135910710x510494
|View full text |Cite
|
Sign up to set email alerts
|

Test expectancy affects metacomprehension accuracy

Abstract: Tests influence students' perceptions of what constitutes learning. Our findings suggest that this could affect how students prepare for tests and how they monitoring their own learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 30 publications
4
87
0
1
Order By: Relevance
“…Moreover, students received explicit information on the kinds of questions they would be asked to answer (i.e., inference questions). This kind of information and experience with inference tests has been shown to improve metacomprehension accuracy of college students (Thiede, Wiley, & Griffin, 2011). This additional instruction was hypothesized to further improve metacomprehension accuracy (Hypothesis 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, students received explicit information on the kinds of questions they would be asked to answer (i.e., inference questions). This kind of information and experience with inference tests has been shown to improve metacomprehension accuracy of college students (Thiede, Wiley, & Griffin, 2011). This additional instruction was hypothesized to further improve metacomprehension accuracy (Hypothesis 2).…”
Section: Methodsmentioning
confidence: 99%
“…Concept map construction is an intervention specifically targeting the situation model. Thiede, Wiley and Griffin (2011) showed that providing instructions about what kind of test to expect and giving practice tests focused college students on appropriate cues and produced more accurate monitoring (see also Thomas & McDaniel, 2007). Two additional advantages arise from assessing the validity of concept map construction as an intervention with a youner population.…”
mentioning
confidence: 99%
“…We chose to have participants select a text for restudy after completing just the inference tests because we wanted to hold test expectancy constant across groups. That is, if test expectancy affects metacognitive monitoring (e.g., Thiede, et al, 2011) it may also effect regulation of study; therefore, failure to hold test expectancy constant could make the regulation data difficult to interpret. We chose to create the expectancy of inference tests in this study because we (and the teachers) wanted to examine regulation for deeper comprehension rather than memory of texts.…”
Section: Methodsmentioning
confidence: 99%
“…Learners may consider the expected test format (and its match with how they are encoding and rehearsing the stimuli) when assigning JOLs and give ratings based upon how well their output strategy aligns with the test format. Prior research supports this idea, as expected test format has an impact on student's mnemonic predictions (and consequently their study choices; Finley & Benjamin, 2012;Thiede, 1996;Thiede, Wiley, & Griffin, 2011). We investigated these three different explanations across two experiments.…”
Section: Monitoring Relatednessmentioning
confidence: 75%